The 500+ Family Program and the objective of the Europe 2020 labour market area - Kryk, Barbara (Program rodzina 500+ a cel z obszaru rynku pracy strategii Europa 2020, 2020)
There is huge controversy around the issue of the impact of the 500+ benefit program on the labour market in Poland, especially on the professional activity of women. The effects in this area are not only relevant for the country but also for the European Union as a whole, as they determine the achievement of the employment goal of the Europe 2020 strategy. It was, therefore, decided to examine this issue more closely. The main goal of the article is to investigate how the 500+ benefit affects the supply of female labour force and the achievement of the employment target of the Europe 2020 strategy. The specific objectives: (1) what were the goals of the Polish government in the area of the labour market at the beginning of the implementation of the EU strategy, and what goals are currently in the Strategy for Responsible Development (SOR)? (2) what were the dynamics of female labour supply compared to the changes in the labour market ? (3) what is the significance of the 500+ program for the trends in the labour market ? (4) what loss (if any) for the economy resulted from the reduction of women’s employment generated? The subject of the study is women’s labour supply/employment, and the subject of research is the Polish economy. To achieve the study goals, the desk research method, time series and indicator analysis, and GDP gaps were used. The research period is 2010-2019, with particular emphasis on the period after the introduction of the benefit in 2016. The research conducted shows that adverse changes in the labour force supply of women caused by the 500+ benefits, were offset by the return to the labour market of previously unemployed or inactive people. Thus, the strategic goal related to employment was achieved.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 9, s. 71-86
Keywords: labour market; women; Family 500+ programme; strategies Europe 2020